The role of motivation, parental support, and peer support in the academic success of ethnic minority first generation college students / Norseha Unin - Unin, Norseha (2012)
The journal article was based on a study done in the American higher education context. Published in the Journal of College Student Development, vol. 46 (3), pages 223-236, “The Role of Motivation, Parental Support, and Peer Support in the Academic Success of Ethnic Minority First Generation College Students” is an article written by Dennis, Phinney, and Chuateco (2005). For this review, I will discuss the strengths, weaknesses, and the conclusions drawn from the article. I will also identify the article’s relation to other works in the same areas of inquiry. The focus is to see how this work fits into a broader intellectual discourse, and the existing literature on the subject of students in postsecondary education.